Financial literacy and investment decisions in Malaysia and United Kingdom: a comparative analysis - Hawati Janor,; Rubayah Yakob,; Noor Azuan Hashim,; Zanariah,; Che Aniza Che Wel, (School of Social, Development and Environmental Studies, Faculty of Social Sciences and Humanities, Universiti Kebangsaan Malaysia, 2016)
In today’s advance and complex financial landscape, financial literacy (FL) is essential as it does not only influence and impact upon financial decisions at the firm level but also a country’s wider financial wellbeing and socioeconomic development . This study compares the FL levels of Malaysia and United Kingdom by utilising the results of the survey from the questionnaire developed by the OECD and by examining demographic and socioeconomic factors that influence the level of FL. The results show that,overall, the level of FL in both countries are low and necessary measures should be taken by the government to increase awareness of financial related matters. The literature findings also reveal that demographic, economic, social, and psychological factors are the main determinants, that some common themes appear with respect to the consequences of FL on investment decisions, demographic factors, methodology and program effectiveness, and that gaps exist in the literature of FL in Malaysia with respect to types of investment and risk tolerance, measurement of financial literacy, methodology and sources of knowledge. The study provides information that may assist in directing future research and in formuling policies and guidelines for policy makers, administrators and educators in incorporating suitable FL components in their training endeavours.